Role Of Rakta Mokshana (Bloodletting) In Various Disease -A Brief Review - patel, Kunal; Vedpathak, Surendra; Bapat, Vaibhav (International Research Journal of Ayurveda & Yoga, 2021)
In Ayurveda, Panchakarma is a very successful Shodhan karma method. Vamana, Virechana, Raktamokshana, and other Shodhan therapies have been identified in the Samhita, with Rakta mokshana being considered the best therapy for Pitta and Rakta Pradoshaj vyadhi. Many Acharya believe that Rakta Dusti is one of the primary causes of Pittaj and Raktaj Vyadhi. Rakta, along with tvak, is usually the leading Dooshya in the range of skin diseases. As an outcome, Raktamokshana using varying modalities is much more effective in resolving pathogenesis in diseases like these. There are numerous historical examples of Raktamokshana being commonly accepted. The indications and contraindications are assessed prior to the procedure. Instruments are completely depended on the surgeon’s skill, the place, the disease, and the availability of instruments. Tools should be modified as required, as per Acharya Sushruta. Since environmental stimuli may trigger Heena-Mithya-Ati Srava of Rakta, it has been advocated in the classics that bloodletting should be performed when the atmosphere is not too cold or too hot. During the operation, the amount of blood to be let out must be determined. According to the classics, one Prastha, Uttama Shodhana, has been suggested. Automatic blood stoppage after a set period of time is a sign of Samyak Siravyadha, which is associated with the patient feeling better and the severity of the illness lowering. As a result of the broad scope, widespread prevalence, and lack of effective management of Rakta Pradoshaj Vyadhi, it is necessary to understand the concept of Raktamokshana in the world of contemporary science and establish the therapy as an effective and safe treatment modality for Rakta Pradoshaj Vyadhi treatment.